Redesain Interior Kantor Dinas Koperasi Usaha Mikro Kecil Dan Menengah Kota Bandung Dengan Pendekatan Lokalitas - Breadlee Pasaribu, Steve; Murdowo, Djoko; Sarihati, Titihan (Telkom University, 2024)
The Office of Micro, Small and Medium Enterprises Cooperative in Bandung City, West Java Province operates in the field of service cooperatives and small-medium business licensing. Surveys indicate issues related to layout and spatial organization, as well as the need to display local culture in the office interior. This design aims to create comfortable, safe spaces that meet community business needs while preserving Sundanese culture as an identity and means of cultural introduction. The research method includes direct observation and interviews at the MSME Office in Bandung City. The design uses a locality approach with the theme